Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Terhadap Kinerja Pegawai : Pada Biro Umum Dan Administrasi Pimpinan Setda Provinsi Papua - Kawer, Lenny Marlina Maria; Risamasu, Ferdinand; Kambu, Arius Andreas (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study aims to analyze the influence of leadership style, motivation, and discipline on employee performance in the General and Administrative Bureau of the Regional Secretariat (Setda) of Papua Province. A quantitative approach with multiple regression analysis was employed to examine the relationships among variables. Data were collected through surveys using questionnaires distributed to employees of the bureau. The results indicate that leadership style has a positive and significant effect on employee performance. Additionally, both work motivation and work discipline positively and significantly influence employee performance. Among these factors, work motivation contributes the most to enhancing employee performance. These findings highlight that improving motivation, implementing effective leadership, and maintaining strict discipline are essential for optimizing employee performance.